2011
DOI: 10.1161/circulationaha.110.985812
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Abnormalities Identified by Cardiovascular Magnetic Resonance Represent a Primary Phenotypic Expression of Hypertrophic Cardiomyopathy

Abstract: Background-Whether morphological abnormalities of the mitral valve represent part of the hypertrophic cardiomyopathy (HCM) disease process is unresolved. Therefore, we applied cardiovascular magnetic resonance to characterize mitral valve morphology in a large HCM cohort. Methods and Results-Cine cardiac magnetic resonance images were obtained in 172 HCM patients (age, 42Ϯ18 years; 62% men) and 172 control subjects. In addition, 15 HCM gene-positive/phenotype-negative relatives were studied. Anterior mitral le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(210 citation statements)
references
References 55 publications
5
180
1
5
Order By: Relevance
“…42 Elongation of the mitral valve leaflets has been previously documented in gene-positive patients irrespective of LVH. 33 However, there have been no studies that have examined the variability in mitral valve leaflet lengths among the specific gene mutations. We have shown that there was no difference in both anterior and posterior mitral valve leaflet lengths between MYH7 and MYBPC3 gene mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Elongation of the mitral valve leaflets has been previously documented in gene-positive patients irrespective of LVH. 33 However, there have been no studies that have examined the variability in mitral valve leaflet lengths among the specific gene mutations. We have shown that there was no difference in both anterior and posterior mitral valve leaflet lengths between MYH7 and MYBPC3 gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior mitral leaflet and posterior mitral leaflet lengths were measured in diastole in the 3-chamber view as described by Maron et al 33 …”
Section: Cmr Analysismentioning
confidence: 99%
“…The method can be applied for follow-up since it is the most accurate method available today to follow changes in left ventricular size, mass and function, to determine left atrial size and function, and the severity of mitral regurgitation. The thickness of the mitral valve can also be defined [35,36] (fig. 2).…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…Maron M.S. и коллеги на данных МР-исследований продемонс-трировали, что длина задней створки у пациентов с ГКМП значимо больше, чем у здоровых субъектов (14±4 против 10±3 мм, p<0,001) [32]. Некоторые ав-торы рекомендуют в качестве пограничного значения нормы длину задней створки 15 мм [23].…”
Section: в) избыточная длина задней створкиunclassified